Evaluating the Outcome of Distal Sodium Channel Block by Chennai Cocktail Composition in Active Phase (Stage 1) of Adhesive Capsulitis (Frozen Shoulder) - Talak Doddabasappa, Mruthyunjaya; Ugrappa , Harish; Iqbal, Roshan; Sanchi, Bharathkrishna; Kumar, Akash (Scripta Medica, 2025)
Background/Aim: The average age range for people with adhesive capsulitis, also referred to as frozen shoulder, is 40–70 years old. Diffuse, severe shoulder pain gradually develops; it usually gets worse at night and causes a progressive loss of range of motion (ROM), particularly external rotation. In the treatment of adhesive capsulitis, distal sodium channel block by the Chennai Cocktail Method has become popular. It works by apparently activating alpha-2 receptors and blocking distal sodium channels, which reduces pain and promotes healing with a low risk of infections and immune reactions. Aim of this study was to evaluate efficacy of this method in patients with adhesive capsulitis. Methods: Chennai cocktail regime consisted of two millilitres (mL) of 2 % lidocaine hydrochloride + 1 mL of 40 mg/mL triamcinolone injection + 30 μg clonidine injection. Prior consent to be taken from the patient before the procedure. Xylocaine, clonidine and steroid test dose were given half an hour before the procedure After the skin was marked, under aseptic precautions parts were painted and draped with a hole towel. Chennai cocktail regime was injected into 1st web space of the affected upper limb. Results: Internal rotation showed the most improvement, while abduction and external rotation showed the fastest and most noticeable recovery. At six weeks and three months, there was a considerable recovery (p < 0.05) in abduction and external rotation. Flexion, abduction and external rotation did not significantly improve at two weeks. The group’s SPADI pain and disability scores significantly improved at six weeks and three months (p < 0.05). Most of the patients were able to return to their normal daily activities and sleep on the affected side without any problems. The VAS showed a significant (p < 0.05) improvement in the group at three months. At three months, flexion, abduction and external rotation all showed a discernible improvement. Conclusion: Injections using the Chennai Cocktail Method for adhesive capsulitis seem to be a safe and efficient treatment that improves ROM and discomfort in individuals with adhesive capsulitis of the shoulder at short-term follow-up.